SPECIFICS OF COGNITIVE-BEHAVIORAL COPING-STRATEGIES AND THEIR CORRELATION WITH COMPONENTS OF REFLEXIVE SYSTEM OF STUDENTS STUDYING UNDER THE PSYCHOLOGICAL SUPERVISION - Klymenko, I. V. (PSYCHOLOGICAL JOURNAL, 2016)
The peculiarities of the cognitive behavioral coping strategies and their interrelation with the components of the reflexivity (reflection ability) showed on the examples of the students which are provided with psychological support while studying in High school. The article analyzes the peculiarities of the cognitive behavioral coping strategies of the students that study in Kharkiv National University of Internal Affairs. There was investigated the interrelation of the components of the reflexivity (reflection ability) of the students which were given the specific psychological treatment while they were studying. The main purpose of such psychological support in High school is full realizationof the individual professional potential of the student, forming the stability in spite of the conditions of the professional environment. The Coping behavior is conscious, purposeful behavior of a person to overcome the problem situation. For this he/she fully analyses and manages the available resources to overcome the situation. The coping strategies – are the set actions that allow people to solve difficult life situations with a help of the actualization of their personal resources when they take into consideration the conditions and environment in which this situation is happening. The reflexivity - a personal ability to focus all activities on him/her self, his/her own characters. Basically the reflection ability is shown up in the process of self-knowledge and self-understanding, so we can talk about the consciousness as a function of the reflection ability in negotiating behavior. After the deep analysis of the coping strategies and the reflexivity of students in conditions of psychological support we can make such conclusions: The students whom were provided with specific psychological treatment have almost all cognitive and behavioral coping strategies than the students who studied in normal conditions. There were found significant interrelation between the indicators of coping strategies and the reflexivity in the groups of students.